Reconciling social enterprise: beyond the paradox perspective. Issue 2 (11th January 2022) - White, Gareth Reginald Terence; Samuel, Anthony; Peattie, Ken; Doherty, Bob
Abstract : Purpose: The paper aims to critically review the increasingly taken-for-granted view of social enterprise (SE) as inherently paradoxical and tackles the research question as follows: are the tensions experienced by SE and social entrepreneurs (SEnt) actually paradoxical and if not, what are the implications for theory and practice? Design/methodology/approach: A paradox theory (PT) approach has been utilized to explore the implications, validity and helpfulness of the paradox perspective in understanding and managing the tensions that are inherent in SE. Findings: Conceptualizing the primary tension of doing social good through commercial activity as a paradox is argued to be a limiting misnomer that conspires to reify and perpetuate the tensions that SE and SEnt have to manage. Drawing upon PT, the findings of the paper reconceptualize these tensions as myths, dilemmas and dialectics, which are subsequently used to develop a more complete ontological framework of the challenges that arise in SE and for SEnt. Practical implications: Reconceptualizing the "inherent paradoxes" of SE as either dilemmas or dialectics affords a means of pursuing their successful resolution. Consequently, this view alleviates much of the pressure that SE managers and SEnt may feel in needing to pursue commercial goals alongside social goals. Originality/value: The work presents new theoretical insights to challenge the dominant view of SE as inherently paradoxical.